Pengaruh Pengawasan, Kompetensi dan Pelatihan Kerja Terhadap Produktivitas Kerja Pegawai Pada Dinas Pendidikan Provinsi Aceh - Helmi Fazli; Lukman T. Ibrahim; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Competence is a factor that influences increasing employee work productivity, work productivity has a relationship with competence. Work productivity is a function of competence, attitudes and actions. Competency is a characteristic of knowledge, skills, behavior and experience to carry out a particular job or role effectively. The aim of this research is to determine the magnitude of the influence of supervision, competency and work training on the work productivity of employees at the Aceh Province Education Service. The data collection technique in this research uses a questionnaire and data analysis uses multiple linear regression. Based on the results of the t test (partial) for the monitoring variable, it has a value of tcount>ttable (2.428>1.566), with a significant value of 0.000 <0.05, then Ha is accepted. The results of the t test (partial) for the competency variable have a value of tcount>ttable (2.862>1.566), with a significant value of 0.000 <0.05, then Ha is accepted and the results of the ttest (partial) for the job training variable have a value of tcount>ttable (3.000 >1.566), with a significant value of 0.000 <0.05, then Ha is accepted. This means that job training has a partial effect on the work productivity of employees at the Aceh Provincial Education Service. Based on the results of the f test (simultaneous), it concludes that the value of Fcount>Ftable is (5.262>2.264), with a significant value of 0.000 <0.05, then Ha is accepted. This means that supervision, competency and job training simultaneously influence the work productivity of employees at the Aceh Provincial Education Service